2020
DOI: 10.1002/cncr.33244
|View full text |Cite
|
Sign up to set email alerts
|

Comparative effectiveness of posttreatment imaging modalities for Medicare patients with advanced head and neck cancer

Abstract: Background Persistent controversy exists with regard to how and when patients with head and neck cancer should undergo imaging after definitive therapy. The current study was conducted to evaluate whether the type of imaging modality used in posttreatment imaging impacts cancer‐specific survival for patients with advanced head and neck squamous cell carcinoma. Methods A retrospective study of National Cancer Institute Surveillance, Epidemiology, and End Results (SEER) program–Medicare‐linked data in patients w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 32 publications
(67 reference statements)
0
4
0
Order By: Relevance
“…Although several medical societies have made recommendations, these mainly depended on expert opinions rather than solid evidence. Furthermore, they did not consider the risk of HNC recurrence, which is greatly dependent on the primary subsite, tumor stage, and molecular markers, such as human papillomavirus (HPV) status . Therefore, assessment schedules are often determined arbitrarily by physicians in daily clinical practice, which produces heterogeneous and inconsistent plans .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although several medical societies have made recommendations, these mainly depended on expert opinions rather than solid evidence. Furthermore, they did not consider the risk of HNC recurrence, which is greatly dependent on the primary subsite, tumor stage, and molecular markers, such as human papillomavirus (HPV) status . Therefore, assessment schedules are often determined arbitrarily by physicians in daily clinical practice, which produces heterogeneous and inconsistent plans .…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, they did not consider the risk of HNC recurrence, which is greatly dependent on the primary subsite, tumor stage, and molecular markers, such as human papillomavirus (HPV) status. 11 Therefore, assessment schedules are often determined arbitrarily by physicians in daily clinical practice, which produces heterogeneous and inconsistent plans. 9 This approach has been associated with over-and undersurveillance of tumor recurrence, thus imposing unnecessary economic and resource burdens on health care systems.…”
mentioning
confidence: 99%
“…Some authors reported incidences of lung SPTs among overall SPTs of up to 39% [ 29 , 30 ] which is similar to our data (29/91 patients or 32%). Among various surveillance imaging tools, FDG PET/CT proved to be the most sensitive [ 31 , 32 , 33 ]. According to some authors, a 12-month PET scan revealed tumor recurrence or SPT in 10% of cases [ 34 ].…”
Section: Discussionmentioning
confidence: 99%
“…Laryngeal cancer patients experience badly impaired vocal, respiratory, and swallowing functions with unfavorable prognoses [ 3 ]. The onset of laryngeal cancer is dormant and most of patients (~ 60%) present with advanced (stage III and IV) disease when diagnosed [ 4 ]. Tendency to local invasion and cervical lymph node metastases badly affect patients’ survival outcomes [ 5 ].…”
Section: Introductionmentioning
confidence: 99%